2021
DOI: 10.17977/jptpp.v6i8.14964
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Permainan Domikado sebagai Teknik Konseling KIPAS untuk Meningkatkan Keterampilan Sosial Siswa Sekolah Dasar

Abstract: <p><strong>Abstract:</strong><strong> </strong>The social skills of elementary school students are currently experiencing problems. Information is obtained based on a need assessment, showing that students have difficulties in social relations in their relationships. Students who experience difficulties in their social life certainly need activities to improve them, one of which is playing. Because playing is an activity that can create social action between individuals, social sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Furthermore, research (S. Putri & Ramli, 2016) revealed that the game of snakes and ladders increases the responsibility of junior high school students. (P. Putri et al, 2018) through their research revealed that to increase self-advocacy, junior high school students can use the dragon snake game containing Bengkulu cultural values.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research (S. Putri & Ramli, 2016) revealed that the game of snakes and ladders increases the responsibility of junior high school students. (P. Putri et al, 2018) through their research revealed that to increase self-advocacy, junior high school students can use the dragon snake game containing Bengkulu cultural values.…”
Section: Discussionmentioning
confidence: 99%
“…2. Pada tahap ini dilanjutkan dengan memberikan strategi konseling berbasis pada budaya yang menjadi ciri khas dari konseling KIPAS dengan mengadopsi dari penelitian (Putri et al, 2021) yaitu permainan Domikado. Teknis permainan domikado sebagai teknik konseling KIPAS ini selain menjadi inovasi layanan klasikal dan sebagai media untuk meningkatkan keterampilan sosial, juga bertujuan untuk mengajarkan siswa tentang pentingnya orang disekitar dalam mencapai proses yang dijalani dan juga melibatkan orang lain dalam mencapai suatu keberhasilan.…”
Section: Siklus Keduaunclassified